Physics and Chemistry Teachers’ Teaching Performance Assessment in the Second Cycle Schools of Basic Education in Damascus - Ahmad, Mahasen (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The research aimed at assessing Physics and Chemistry Teachers’ Teaching Performance Assessment in the Second Cycle Schools of Basic Education in Damascus, during the second semester of the academic year 2017/2018. The study sample included (30) male and female teachers. The descriptive analytical research method was used through designing performance scorecard; and the questions were formed as follows: What is the physics and chemistry teachers’ performance level in terms of: - Classroom management; - Presenting and activating lesson content using varied/differentiated and appropriate teaching methods; - Deepening students’ scientific values; - Training students to use the acquired knowledge functionally. - Provide students with mental skills. - Conduct the interim and final evaluation as appropriate. Are there statistically significant differences in physics and chemistry teachers’ performance due to gender variable? 3. Are there a statistical difference in the performance of physics and chemistry teachers due to the variable of scientific qualification (University degree, Diploma of educational qualification( The research conclusions demonstrated that: The conclusions of the teachers’ performance scorecard showed discrepancy in executing the items included in the scorecard. No statistically significant differences in teachers’ performance due to gender differences. There are statistically significant differences in teachers’ performance due to differences in degrees/ qualifications.